THE ROLE OF FIELD IN DEALING THE CULTURE OF SIDE AND TATOBY OF THE NIFAS MOTHER IN THE TIMOR IN THE CENTRAL MOLLO DISTRICT TIMOR SOUTH CENTRAL DISTRICT 2016 - ASTIN NUR HANIFAH (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2016)
Background: Riskesdas 2013 data show that 43.2% of births are still at home. This situation leads to the risk of delay in obtaining services in case of obstetric and neonatal complications. According to WHO data, about 15-20% of pregnancies have a risk of complications that require adequate emergency care. Therefore, the readiness of healthcare facilities in Poskesdes or in the Midwife of Independent Practice (BPM) is needed. The culture of the Timorese Timor Tengah Selatan (TTS) is the mother is required to give birth at home round and get treatment for 40 days by a shaman or someone who is believed to have experience of caring for the mother of childbirth. Treatment of postpartum is usually a taboo of certain foods, roasted fire, and tatobi. The provision or restriction to be followed by the puerperal mother is not allowed to go out for 40 days except to the bathroom. The midwife's midwife competency is midwives providing high-quality and comprehensive care to families, groups, and communities in accordance with the local culture. As midwives in the midwife community must be able to recognize the cultures that exist in the community and should be able to determine which culture is still applicable to mothers and cultures that are detrimental to mothers and infants, besides the midwife is required to play an active role in facing the culture so as to improve the welfare mother and infant matching goals 4 and 5 of MDG's. Objective: To identify the role of midwives in the community in dealing with TTS TTS district culture about the culture of roast and tatobi in the postpartum year 2016.Types of Research: Based on research purposes researchers used descriptive research type with a qualitative approach. Result: The mothers in Mollo Tengah village community still adhere to the grilled and tatobi tradition of the mothers in the village community of Central Mollo Panggang they do at home round. The process of roasting at home round is also trusted by the local community for the antidote to severe pain especially in women after the birth process. Another reason that the underlying baked fire or tatobi is the concern of parents when the child's body condition becomes weak and not strong even will cause madness in the mother of the maternity. But in reality, this will be bad, not only the possibility of mother and baby will burn his body and affect the healing of wounds after giving birth. In addition, due to the environment of the house that is less clean because of all the activities for the care done in the house, such as cooking and roasting so that mothers and babies at risk of ARI. Some of the activities performed by the midwife at the Central Mollo district health center are refreshing cadres, including asking the help of health cadres and shamans to disseminate information about the loss of abstinence, safe bake by paying attention to the distance of embers with maternal beds, and tatobi only by using water just warm up. In addition, health cadres are also invited to do data mapping of target KIA (pregnant women, postpartum, babies, and toddlers) in the community and the provision of PMT. Discuss tubulin and also discuss the waiting house so that the waiting house can be functioned properly.